2010
DOI: 10.1111/j.1365-3024.2010.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of modulation of experimental autoimmune encephalomyelitis by chronic Trichinella spiralis infection in Dark Agouti rats

Abstract: Trichinella spiralis is a helminth that provokes Th2 and anti-inflammatory type responses in an infected host. Our previous studies using Dark Agouti (DA) rats indicated that T. spiralis infection reduced experimental autoimmune encephalomyelitis (EAE) severity in rats. The aim of this study was to analyse the mechanisms underlying EAE suppression driven by T. spiralis infection. Reduced clinical and histological manifestations of the disease were accompanied by increased IL-4 and IL-10 production and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 49 publications
(61 reference statements)
2
65
0
2
Order By: Relevance
“…An expansion of CD4 ϩ Foxp3 ϩ Tregs is also seen in other gastrointestinal parasite infections of mice, including Strongyloides ratti in the intestine (28), and around the muscle-stage larvae of Trichinella spiralis (25) or in the spleen of rats similarly infected (104). The depletion of Tregs in DEREG mice immediately after infection with S. ratti resulted in the expression of protective immunity (28), but the depletion of Tregs using anti-CD25 antibody during T. spiralis infection results only in increased Th2 responses without affecting parasite burden.…”
Section: Cd25mentioning
confidence: 99%
“…An expansion of CD4 ϩ Foxp3 ϩ Tregs is also seen in other gastrointestinal parasite infections of mice, including Strongyloides ratti in the intestine (28), and around the muscle-stage larvae of Trichinella spiralis (25) or in the spleen of rats similarly infected (104). The depletion of Tregs in DEREG mice immediately after infection with S. ratti resulted in the expression of protective immunity (28), but the depletion of Tregs using anti-CD25 antibody during T. spiralis infection results only in increased Th2 responses without affecting parasite burden.…”
Section: Cd25mentioning
confidence: 99%
“…Fare modellerinde H. polygyus, S. mansoni, T. spiralis ve Fasciola hepatica ile öncül infeksiyonların otoimmün ensefalomiyelit gelişimini etkilediği gözlemlenmiştir [40][41][42][43] . Sewell ve arkadaşları ile Gruden-Movsesijan ve arkadaşları, indüklenen T H 2 immün yanıtın önemini vurgularken Wilson ve arkadaşları ile Walsh ve arkadaşları sırasıyla B reg ve T reg hücrelerin etkin olabileceğini rapor etmişlerdir [41][42][43][44] .…”
Section: Multipl Sklerozunclassified
“…Sewell ve arkadaşları ile Gruden-Movsesijan ve arkadaşları, indüklenen T H 2 immün yanıtın önemini vurgularken Wilson ve arkadaşları ile Walsh ve arkadaşları sırasıyla B reg ve T reg hücrelerin etkin olabileceğini rapor etmişlerdir [41][42][43][44] . Bunun yanında Gruden-Movsesijan ve arkadaşları ile Welsh ve arkadaşları T. spiralis ve H. polygus ile infekte edilen fareden alınan mezenter lenf düğüm hücrelerinin ve splenositlerin otoimmün ensefalomiyelit gelişiminde gerilemeye sebep olabileceğini öne sürmüşlerdir [42,43] . Ensefalomiyelit gelişiminde rolü olduğu gösterilen bir diğer helmint de S. mansoni yumurtası olup T H 2 immün yanıtını uyararak etkili olduğu düşünül-mektedir [41] .…”
Section: Multipl Sklerozunclassified
“…In the present study, we used immunohistological staining and Western blots to detect T. spiralis antigens that cross-react with autoantibodies. These data allow us to identify the structures that we should focus on in future investigations of the recently described T. spiralis-mediated amelioration of EAE (Gruden-Movsesijan et al 2008, 2010. We found that a large proportion of autoantibody-containing human sera recognized T. spiralis antigens.…”
mentioning
confidence: 99%
“…From this immunoprivileged site, muscle larvae produce excretory-secretory products (ES L1) that manipulate the host immune response to other, irrelevant antigens and limit the inflammatory response (Fabre et al 2009). Infection with T. spiralis (Khan et al 2002, Saunders et al 2007, Gruden-Movsesijan et al 2010 or treatment with a T. spiralis antigen preparation (Motomura et al 2009) may prevent the development of several autoimmune diseases, such as type 1 diabetes, experimental autoimmune encephalomyelitis (EAE) and experimental colitis, by skewing the immune response towards a Th2 or regulatory profile. Studies of the mechanisms underlying the amelioration of autoimmunity that is observed during T. spiralis infection have focused on both the immune system and parasite molecules involved in immune modulation.…”
mentioning
confidence: 99%